2009
DOI: 10.1063/1.3153978
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of GaAs(001) surfaces thermally annealed in dry N2 atmosphere

Abstract: Thermal annealing behaviors of GaAs͑001͒ surfaces in dry N 2 atmosphere have been studied by using spectroscopic ellipsometry ͑SE͒, optical microscopy, scanning electron microscopy, ex situ atomic force microscopy ͑AFM͒, x-ray photoelectron spectroscopy ͑XPS͒, and photoluminescence ͑PL͒ techniques. The SE data indicate that thermal annealing at temperatures T below 500°C causes no or a little influence on the surface morphology. Microscopic roughening starts to occur at T Ͼ 600°C and exhibits a saturated rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
1
0
2
Order By: Relevance
“…It was found that arsenic atoms concentration also decreases during thermal annealing, the same results were described in [17]. Any arsenic oxides that may be formed via this elemental arsenic diusion to the surface are likely to be highly unstable and therefore easily evaporate.…”
Section: Resultssupporting
confidence: 68%
“…It was found that arsenic atoms concentration also decreases during thermal annealing, the same results were described in [17]. Any arsenic oxides that may be formed via this elemental arsenic diusion to the surface are likely to be highly unstable and therefore easily evaporate.…”
Section: Resultssupporting
confidence: 68%
“…However, the effects of semiconductor surfaces on their luminescent properties have received little attention. Although a few reports showed the surface conditions affecting their luminescent properties, 3,4) no clear or conclusive evidence has been presented, yet to our knowledge. In order to improve the intensity of GaN LEDs, we should focus on the surface effects on the luminescence efficiency.…”
Section: Introductionmentioning
confidence: 89%
“…Чистая поверхность необходима для последующего проведения различных процессов эпитаксиального выращивания и нанесения диэлектрических покрытий. Основной проблемой является высокая термическая устойчивость оксидов атомов III группы, что не позволяет эффективно использовать отжиг в вакууме для очистки поверхности полупроводников [91][92][93]. Ионное распыление и различные методы " сухого" травления приводят, как правило, к существенному разупорядочиванию поверхности и к появлению большого количества дефектов, а в случае твердых растворов и к значительному изменению состава и, как следствие, объемных свойств полупроводника [26,27].…”
Section: методы удаления слоя собственного окисла с поверхности полупunclassified